2016
DOI: 10.1007/s10067-016-3468-6
|View full text |Cite
|
Sign up to set email alerts
|

Does addition of glucocorticoids to the initial therapy influence the later course of the disease in patients with early RA? Results from the Swiss prospective observational registry (SCQM)

Abstract: The main goal of this study was to analyse whether initial addition of glucocorticoid to DMARD therapy influences the long-term course of the disease in patients with early rheumatoid arthritis. All patients from the Swiss RA cohort SCQM with recent-onset arthritis (disease duration ≤1 year) were analysed. The exposure of interest was the use of glucocorticoids (GCs) at baseline. As primary outcome, we considered clinical and radiographic disease progression, assessed by the disease activity (disease activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…therefore, may not be generalizable to patients starting GC together with csDMARD, implying that caution must be taken when comparing the results from our analysis to other trials in which patients were GC-naive prior to the commencement of the study. Further, it has previously been reported that rheumatologists may be more likely to initiate GC in patients with more severe RA 39 . Although the baseline characteristics of patients in our analysis were generally similar, it is possible that the patients with RA receiving GC were less responsive to treatment than the patients who were not initially receiving GC.…”
Section: Discussionmentioning
confidence: 97%
“…therefore, may not be generalizable to patients starting GC together with csDMARD, implying that caution must be taken when comparing the results from our analysis to other trials in which patients were GC-naive prior to the commencement of the study. Further, it has previously been reported that rheumatologists may be more likely to initiate GC in patients with more severe RA 39 . Although the baseline characteristics of patients in our analysis were generally similar, it is possible that the patients with RA receiving GC were less responsive to treatment than the patients who were not initially receiving GC.…”
Section: Discussionmentioning
confidence: 97%
“…As a result, software automatically flagging drug interactions cannot assist prescribers. To address this concern, clinicians may stop medical cannabis in order to avoid these interactions when starting new medications, a problem that may be exacerbated in states making available smoked cannabis which contains over 100 phytocannabinoids (i.e., natural plant products) [21]. Although the evidence for significant drug interactions with THC and CBD is rare, THC and CBD are metabolized by CYP1A2, CYP2C9, CYP2C19, and CYP3A4 and serum concentrations of these molecules may theoretically increase with medications that inhibit or induce these enzymes [22].…”
Section: Discussionmentioning
confidence: 99%
“…According to Swiss registries, the use of fırst-line CS was significantly higher (25.5% versus 68%) in patients with EORA compared with those with YORA, while the use of biological drugs during follow up was much lower. 49 Genevay and colleagues evaluated 1571 patients with RA (344 over 65 years old) receiving anti-TNFα drugs. 50 Drug withdrawal rates and mean Disease Activity Score (DAS28) score changes were similar in both groups at the end of the second year.…”
Section: Treatmentmentioning
confidence: 99%